(3efThQ GdTjN CHj GdeYGdi GdWGgQs - (3CHh GdeYGdi GdeWGgQs; (3GdbhUhfj , TeS GdOjf eMeO Hf eMeO Hf eMeO Hf HOQ GdOjf GdbhUhfj,J (B931 (3g` s
(3ChdgG (B:s
(3HSe GdEdg GdbGOQ hef bQH CLd GdfGcK GdcGaQ CWGd Gddg HbGA GdTjN GdaGVd bO EJSYJ WQb GdeWGde s
(3BNQgG (B:s
(3hgh GdefJbe eef HGf ef GdNQUI GdeOYjjf hjUd HbQH GdLGeY GdGRgQ hGdMeO dehdGfG hMOg hGdTcQ dbGFe GdReGf YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B260s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3abg GdePGgH GdCNQis